7 - Côte d’Ivoire: L’Etat et l’économie parallèle: by Youetto Raymond - Youetto Raymond (Africa Development, 1994)
Like most all Third World countries , Côte d'Ivoire is also caught in the development of what can be termed as a 'Second economy ' This economy is carried out illegally and invisibly - National statistics can hardly take it into account. However , it cannot operate without the official economy. It is an economy within an economy. This economy corresponds to a change of behaviour originating from the necessity to resist some constraints either by creating parallel markets or trying to obtain additional funds in order to cope with economic difficulties. In both cases the results are just bad for the economy of Côte d* Ivoire because it looses in public incomes and professional taxes while at the same time encouraging nepotism and treacherous financial dealings. The major issue to consider now is whether this is the negative outcome of capitalism when some business aspects of market economy are brutally introduced in a state of underdevelopment or the mere negative results of an inefficient but conscious and deliberately conceived mode of management to perpetuate delapidation of public funds. The paper advises that the State should limit and control this parallel economy.